Characterization of a Drought-Inducible Dehydrin Promoter from Sugarcane (Saccharum officinarum L.) in Tobacco (Nicotiana tabacum L.) - Iskandar, Hayati Minarsih; Suhandono, Sonny; Pambudi, Jembar; Kristianti, Tati; Putranto, Riza Arief; Mose, Windi; Sustiprijatno, Sustiprijatno (Journal of Tropical Crop Science, 2020)
Dehydrin (DHN) is known to play an important role in plant response and adaptation to abiotic stresses (drought, high salinity, cold, heat, etc.). Previous research reported the increased expression of DHN in sugarcane stems exposed to drought stress for 15 days which may be controlled by its corresponding stress inducible promoter. The DHN promoter was succesfully isolated from sugarcane variety PSJT 941 (Pr-1DHNSo) and was cloned to pBI121 expression vector fused to a β-glucuronidase (GUS) reporter gene. The aim of this research was the functional testing of the Pr-1DHNSo promoter through transformation into tobacco plant treated with in vitro drought stress. Genetic transformation of Pr-1DHNSo construct was conducted by Agrobacterium tumefaciens. The transformed tobacco was then subjected to drought stress treatment using 40% PEG 6000 for five sequential incubations (0, 12, 24, 48 and 72 hours). The GUS assay reveal that the transformed tobacco treated with drought stress showed a blue color denoting GUS activity in leaf, stem and root tissues and this expression increased along with the length of the drought treatment. The analysis of gusA gene using real time-qPCR normalized to the L25 reference gene also showed that the expression increased in line with the length of time of drought stress. The results presented in this study indicated that the Pr-1DHNSo promoter from sugarcane was expressed and induced by drought stress treatment in tobacco.